GURU: DIGUGU DAN DITIRU - Ghofar, Abdul (Universitas Ahmad Dahlan, 2017)
The paper intitled: ?Teachers: Obeyed and Imatated ? describes how criteria and requirement for any requirements that must be possessed by the teacher so that he becomes a teacher who is heard his advice and obeyed all his orders, as well as his behavior could be an example for his student . He is a professional teacher.To be a professional teacher then he shoud seek as optimal as possible to meet the competencies that must be owned by a teacher. The competencies include professional competence, pedagogical competent, social competence and personal competence as well he should be healthy physically and spiritually. Profesional teachers are teachers who are able to manage themselves in carrying out their duties daily.Criteria professional teachers include : 1) having tellent as a teacher, 2) having skill as ateacher, 3) having a good as expertise and integrated, 4) having a healthy mental, 5) able-bodied, 6) having extensive experience and knowledge, 7)having spirit of Pancasila, 8) the teacher is a good citizen.There are four programs that can be developed in the framework of the establishment of professional teachers, namely 1) pre-service education; 2) in-service education; 3) in-service training; and 4) on-service training.